Adherence to treatment for diabetes mellitus: validation of instruments for oral antidiabetics and insulin - Lilian Cristiane Gomes-Villas Boas; Maria Luisa Soares Almeida Pedroso de Lima; Ana Emilia Pace (Universidade de São Paulo, 2014)
OBJECTIVES: to verify the face validity, criterion-related validity and the reliability of two distinct forms of presentation of the instrument Measurement of Adherence to Treatment, one being for ascertaining the adherence to the use of oral antidiabetics and the other for adherence to the use of insulin, as well as to assess differences in adherence between these two modes of drug therapy. METHOD: a methodological study undertaken with 90 adults with Type 2 Diabetes Mellitus. The criterion-related validity was verified using the Receiver Operating Characteristic curves; and for the reliability, the researchers calculated the Cronbach alpha coefficient, the item-total correlation, and the Pearson correlation coefficient. RESULTS: the oral antidiabetics and the other showed sensitivity of 0.84, specificity of 0.35 and a Cronbach correlation coefficient of 0.84. For the adherence to the use of insulin, the values found were, respectively, 0.60, 0.21 and 0.68. A statistically significant difference was found between the final scores of the two forms of the instrument, indicating greater adherence to the use of insulin than to oral antidiabetics. CONCLUSION: it is concluded that the two forms of the Measurement of Adherence to Treatment instrument are reliable and should be used to evaluate adherence to drug treatment among people with diabetes mellitus.